Effects of bilateral and unilateral plyometric training on physical performance in male postpubertal basketball players 4o - Aztarain-Cardiel, K.; Garatachea, N.; Pareja-Blanco, F. (International Journal of Sports Physiology and Performance, 2025)
Purpose: The aim of this study was to analyze the effects of bilateral and unilateral plyometric-training (PT) programs on jumping, sprinting, and change-of-direction (COD) ability in male postpubertal basketball players.